Trichodysplasia spinulosa-Associated Polyomavirus Uses a Displaced Binding Site on VP1 to Engage Sialylated Glycolipids. - Luisa J Ströh (PLoS Pathogens, 2015)
Trichodysplasia spinulosa-associated Polyomavirus (TSPyV) was isolated from a patient suffering from trichodysplasia spinulosa, a skin disease that can appear in severely immunocompromised patients. While TSPyV is one of the five members of the polyomavirus family that are directly linked to a human disease, details about molecular recognition events, the viral entry pathway, and intracellular trafficking events during TSPyV infection remain unknown. Here we have used a structure-function approach to shed light on the first steps of TSPyV infection. We established by cell binding and pseudovirus infection studies that TSPyV interacts with sialic acids during attachment and/or entry. Subsequently, we solved high-resolution X-ray structures of the major capsid protein VP1 of TSPyV in complex with three different glycans, the branched GM1 glycan, and the linear trisaccharides α2,3- and α2,6-sialyllactose. The terminal sialic acid of all three glycans is engaged in a unique binding site on TSPyV VP1, which is positioned about 18 Å from established sialic acid binding sites of other polyomaviruses. Structure-based mutagenesis of sialic acid-binding residues leads to reduction in cell attachment and pseudovirus infection, demonstrating the physiological relevance of the TSPyV VP1-glycan interaction. Furthermore, treatments of cells with inhibitors of N-, O-linked glycosylation, and glycosphingolipid synthesis suggest that glycolipids play an important role during TSPyV infection. Our findings elucidate the first molecular recognition events of cellular infection with TSPyV and demonstrate that receptor recognition by polyomaviruses is highly variable not only in interactions with sialic acid itself, but also in the location of the binding site.